Pengaruh Influencer Marketing dan Kualitas Produk Terhadap Brand Awareness Produk Scarlett Whitening: Studi Kasus pada Pengikut Akun Scarlett Whitening di Aplikasi Tiktok - Talenta Aulia Moekti; Ety Dwi Susanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine and analyze the influence of influencer marketing and product quality simultaneously on brand awareness of Scarlett Whitening products among followers of the Scarlet Whitening account on the TikTok application. In this research, the type used is quantitative research. This quantitative object emphasizes the analysis of data in the form of numerical or numbers processed using statistical methods to determine the influence of one variable on other variables. With the results of this research which shows how brand awareness of Scarlett Whitening products has increased among followers of the Scarlett Whitening account on the TikTok application (2023) due to the influence of many influencers who provide content that is interesting, good, unique and in line with the values ​​provided by the brand, consumers will more interested in reviewing it and even sharing it so that the reach given will be wider, thus influencing brand awareness of Scarlett Whitening. Of course, brand awareness itself has the aim of making the brand a leading product or top of mind product so that it will be easily recognized by consumers and increase sales of Scarlett Whitening.